Climate Change, New Security Challenges and the United Nations. - Mohapatra, Sabita (Taylor & Francis Group, 2018)
"Climate change affects human health in all sectors of society, both domestically & globally. The sea-level rise, changes in precipitation resulting in flooding & drought, heat waves, more intense hurricanes & storms, and degraded air quality, affect human health. This book is an attempt to unravel the new non-traditional challenges that the UN will face in coming decades if the states fail to keep the climate change fixed at the threshold of 2 degrees Celsius as agreed at the COP 21 conference in Paris by all the states results in intra and inter-state conflict. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka."- Resumé vydavatel